Balancing work and private life: when does workplace flexibility really help? New insights into the interaction effect of working from home and job autonomy - Baum, Lisa; Rau, Renate (Frontiers in Organizational Psychology, 2024)
Introduction Empirical research has reported variable and inconsistent findings regarding the relationship between working from home (WFH) and work-life balance (WLB). We propose that the inconsistency in the relationship between WFH and WLB may be due to unexplored moderators of this relationship. The work characteristic “job autonomy,” defined as the degrees of freedom in terms of time and content, is examined as one such possible moderator. We address the question of whether different types of negative spillover (strain-based and time-based spillover) from work to private life are dependent on an interaction effect between the use of WFH and job autonomy. Method Experienced occupational psychologists analyzed heterogeneous workplaces in an organization over a whole shift using a task-related instrument (TAG-MA: Tool for task analyses and job design in jobs with mental work requirements). The degrees of freedom in terms of content and time were assessed within this. Online questionnaires were used to measure WFH use, perceived job demands, and negative spillover from work to private life. Four moderator models were tested in a sample of 110 employees from various occupations. Results The results show that WFH is associated with a decrease in negative work-life spillover, especially when people have limited autonomy at work. Discussion The results are discussed and differentiated in more detail for the different types of spillover. The implications for health-promoting work design are derived.